TRANSITIVITY IN MATERIAL, MENTAL, AND VERBAL PROCESSES IN THE E-BOOK TEXT 电子商务基础 / DIÀNZǏ SHĀNGWÙ JĪCHǓ - Valentina, Tasya; Alindra, Devi Alvionita (Faculty of Letters Universitas Balikpapan, 2026)
This study aims to examine the occurrence of material, mental, and verbal processes in the text of the e-book 电子商务基础 / E-commerce Basics by employing the framework of Systemic Functional Linguistics (SFL), with a particular focus on the transitivity system. Within SFL, transitivity explains how human experience is represented in language through different process types, participant roles, and accompanying circumstantial elements. The research adopts a descriptive qualitative method, with data collected through literature review of the first three chapters of the book. The findings show that material processes are the most dominant, indicating that the text primarily focuses on real actions and activities in the world of e-commerce. Mental processes reflect the thoughts, perceptions, and feelings of consumers and business actors, while verbal processes describe communication and interactions within digital business activities. The analysis demonstrates that transitivity theory effectively reveals both explicit and implicit meanings in the e-commerce text and enhances understanding of how language structures and conveys meaning in a digital business context.